Prediksi jumlah pengunjung webstie resmi Kabupaten Malang menggunakan metode autoregresive integreted moving average - Priyani, Lengga (Maliki Interdisciplinary Journal, 2024)
This study aims to predict the number of visitors to the official website using the ARIMA (Autoregressive Integrated Moving Average) method. Visitors to the official website are an important indicator in measuring the level of interaction and public interest in the information provided by local governments. In order to improve forecasting accuracy, the first step is to analyze visitor historical data to identify patterns and trends that may exist. Next, testing the stationarity of the data using ACF (Autocorrelation Function) and PACF (Partial Autocorrelation Function) to determine the correct forecasting steps. From the results of the analysis, it was found that the official website visitor data does not have a stationary nature, so it is necessary to do differencing to get stationary data in order to build the ARIMA model. After that, the next step is to determine the most suitable ARIMA model parameters by analyzing the ACF and PACF values from the differentiated data. With the specified model parameters, the validity of the ARIMA model is tested using actual visitor data.